Links Between Internal Factors, External Factors, Implementation Of Standard Operational Procedure (SOP) with Shallot Farmers Productivity in Bondowoso - Ida Rahayu; Ridwan Iskandar; Rahmat Ali Syaban (Kadiri University - Faculty of Agriculture, 2023)
The purpose of this study was to analyze the farmer's internal and external factors on shallot productivity through the implementation of Standard Operating Procedures (SOP) for shallot cultivation as an intervening variable in Bondowoso Regency. The research method is descriptive quantitative, with data collection methods using primaryand secondary data. The research technique uses path analysis (Path Analysis) using SPSS 22.0. The results of the analysis show that there is a significant influence of internal factors (X1) on shallot cultivation SOP (Z). This is based on the probability-value which is smaller than alpha (0.000 <0.05), external factor variables (X2) have a significant effect on cultivation SOP (Z). This is indicated by the probability-value which is smaller than alpha (0.000<0.05). The internal factor variable (X1) has a significant effect on shallot productivity (Y). This can be seen from the probability-value which is smaller than alpha (0.013 <0.05). There is a significant influence between external factor variables (X2) on shallot productivity (Y) this is indicated by the probability-value smaller than alpha (0.018<0.05), as well as shallot cultivation SOP variable (Z) on shallot productivity (Y) because the probability-value is smaller than alpha (0.000 <0.05) so there is a significant influence between the shallot cultivation SOP variable (Z) on shallot productivity (Y). So it can be concluded that there is a significant influence between internal and external factors, through SOPs on shallot productivity in Bondowoso. Recommendations for shallot farmers in Bondowos to follow SOP for shallot cultivation as a whole to increase shallot productivity.